2016
DOI: 10.1177/0013916516663796
|View full text |Cite
|
Sign up to set email alerts
|

A Household Is Not a Person: Consistency of Pro-Environmental Behavior in Adult Couples and the Accuracy of Proxy-Reports

Abstract: Studies on environmental behavior commonly assume single respondents to represent their entire household or employ proxy-reporting, where participants answer for other household members. It is contested whether these practices yield valid results. Therefore, we interviewed 84 couples, wherein both household members provided self-and proxy-reports for their partner. For use of electrical household appliances, consumption of hot water, space heating, everyday mobility, and environmental values, many variables fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 39 publications
1
36
0
1
Order By: Relevance
“…On a related point, whereas electricity consumption was-for practical reasons-assessed on the household level, ecological lifestyle was measured for individuals (i.e., the person holding the contract with the EPC). As couples living in one household are sometimes found to report quite differential engagement in specific environmentally protective activities (see, for example, Seebauer, Fleiß, & Schweighart, 2016), this discrepancy in level of measurement creates some uncertainty regarding the actual magnitude of the relation between people's ecological behavior and electricity consumption (Yang, Shipworth, & Huebner, 2015). However, it is likely to have deflated rather than increased the correlation of interest.…”
Section: Limitationsmentioning
confidence: 99%
“…On a related point, whereas electricity consumption was-for practical reasons-assessed on the household level, ecological lifestyle was measured for individuals (i.e., the person holding the contract with the EPC). As couples living in one household are sometimes found to report quite differential engagement in specific environmentally protective activities (see, for example, Seebauer, Fleiß, & Schweighart, 2016), this discrepancy in level of measurement creates some uncertainty regarding the actual magnitude of the relation between people's ecological behavior and electricity consumption (Yang, Shipworth, & Huebner, 2015). However, it is likely to have deflated rather than increased the correlation of interest.…”
Section: Limitationsmentioning
confidence: 99%
“…Although most policy measures related to energy efficiency affect households as units without much regard to their structure, the make-up of the household and the differing beliefs and behaviors of their members are determinants of the actual energy consumed or conserved by the household. Household members may even engage in conflicting actions depending on their preferences and everyday activities, thus it could be important to be aware of the behaviors and values of individuals living within the same household (Seebauer, Fleiß, & Schweighart, 2017). As of now, related studies seem to have mainly focused on differences and similarities between members of families and couples living in one household (Longhi, 2013;Seebauer et al, 2017;Thøgersen & Grønhøj, 2010).…”
Section: The Role Of Households Shared Housing and Student Householdsmentioning
confidence: 99%
“…Finally, looking at the broader literature, as household energy use cannot be determined based on a single person's actions, it should be rather examined based on the actions of other household members (Seebauer et al, 2017). Also, as we don't know whether influence behaviors have the intended resultthat is, whether the person intended to be influenced will act in accordance with the message of the influencerdeterminants of success of this type of action could also be examined.…”
Section: Limitations and Directions For Further Researchmentioning
confidence: 99%
“…In the field of environmental behavior, Seebauer et al (2017) revealed the proxy-response bias of household energy conservation and pro-environmental values. In their examination of travel behavior, bias was higher for shopping or leisure trips than work trips.…”
Section: Proxy Response In General Surveysmentioning
confidence: 99%